A Trinity Analytical Framework for ISDS Reform. (24th September 2018) - Shan, Wenhua; Feng, Yunya
Abstract : The American Journal of International Law 's recent articles on the reform of investor-state dispute settlement (ISDS) make important contributions to ongoing debates. The article by Sergio Puig and Gregory Shaffer elaborates on the methods of investment dispute resolution—the various institutional innovations that states might pursue to improve the system. The essay by Anthea Roberts in turn explores the subjects of investment dispute resolution—states and their varying positions on reform. In our essay, we supply a third perspective by discussing the objects of ISDS—that is, the disputes themselves, which vary considerably from one case to another. We believe that considering methods, subjects, and objects together—what we refer to as a "trinity analytical framework"—could assist states as they formulate their positions in the reform process going forward. At the same time, we do not think that all reform options are equally meritorious, and we critique Puig and Shaffer's proposal for complementarity between municipal courts and international mechanisms as at best premature.